Synthesis, structure and electric properties of a new lead-free ferroelectric solid solution of (1−x)BaTiO3–xBi(Zn2/3Nb1/3)O3. (July 2015) - Paterson, Alisa; Wong, Hoi Ting; Liu, Zenghui; Ren, Wei; Ye, Zuo-Guang
Abstract: Ceramics of a novel lead-free ferroelectric solid solution, (1− x )BaTiO3 – x Bi(Zn2/3 Nb1/3 )O3 [(1- x )BT– x BZN], have been prepared with x =0–0.125 and their structure and dielectric properties investigated. The effects of BZN substitution for BT on the crystal structure and dielectric and ferroelectric properties are examined. The structure at room temperature is refined to be tetragonal for x ≤0.025, a mixture of rhombohedral and tetragonal phases for x =0.05, and pseudo-cubic for x ≥0.075. As the BZN content increases, the Curie temperature T C of the solid solution decreases, and the phase transition becomes more diffuse. At x =0.075, relaxor-like behavior appears. The diffuseness of the phase transition and the crossover from ferroelectric to relaxor character are attributed to increased cationic disorder arising from the aliovalent coupled substitutions of Bi 3+ for Ba 2+ and (Zn2/3 Nb1/3 ) 3+ for Ti 4+ . A partial phase diagram of the solid solution is established.